ANTESEDEN MINAT LOYALITAS - Karina Putri, Noventia; Widiyanto, Ibnu (Diponegoro Journal of Management, 2015)
This research is motivated by the higher rate of growth of SMEs among the students especially in culinary field. The purpose of this study is to analyze the effect of price perception, the attractiveness of the product, and responsiveness of employees on customer satisfaction and the implications for loyalty interest of Takoyaki 48.The population in this research is the consumers of Takoyaki 48 Semarang. The sample is taken from 130 respondents. The result showed that three of the independent variables directly influencing customer satisfaction, but only one of those which had directly influencing to customer loyalty, that was price perception. Consistent with the previous studies, customer satisfaction has positive relation and significantly mediates the effect of independents variables to engage customer loyalty.